Highly selective palladium-catalyzed Stille coupling reaction toward chlorine-containing NIR electroluminescent polymers1. Issue 28 (28th July 2015) - Zhang, Yubao; Gao, Xiang; Li, Junli; Tu, Guoli
<x xml:space="preserve">Abstract</x> Chlorine-containing conjugated polymers were obtained by the optimized Stille coupling reaction; non-doped PLEDs of the polymers exhibited NIR emission.